2010
DOI: 10.1111/j.1600-0668.2010.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particle concentrations and exposures in six elementary school classrooms in northern California

Abstract: This study provides data and insight concerning the UFP exposure levels children may encounter within classrooms and the factors that most significantly affect these levels in an urban area in northern California. This information can serve as a basis to guide further study of children's UFP exposure and the potential associated health risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 31 publications
(41 reference statements)
4
89
4
1
Order By: Relevance
“…In contrast, studies on UFP in 39 primary schools in Spain Rivas et al, 2014), 7 primary schools in Greece (Diapouli et al, 2007), and 2 primary schools in Italy (Buonanno et al, 2013b) reported 1.2-to 3.5-fold higher values of UFP. Similarly, studies from other non-European countries such as in California (Mullen et al, 2011), Australia (Morawska et al, 2009), and South Korea (Kim et al, 2011) noted considerably higher levels of UFP than the findings obtained in the cur-rent investigation. These differences may be associated with seasonal influences, meteorological conditions, or specific characteristics of the environment where schools are located, such as level of development, urbanization, and traffic (World Health Organization [WHO] 2006).…”
Section: Discussionsupporting
confidence: 49%
“…In contrast, studies on UFP in 39 primary schools in Spain Rivas et al, 2014), 7 primary schools in Greece (Diapouli et al, 2007), and 2 primary schools in Italy (Buonanno et al, 2013b) reported 1.2-to 3.5-fold higher values of UFP. Similarly, studies from other non-European countries such as in California (Mullen et al, 2011), Australia (Morawska et al, 2009), and South Korea (Kim et al, 2011) noted considerably higher levels of UFP than the findings obtained in the cur-rent investigation. These differences may be associated with seasonal influences, meteorological conditions, or specific characteristics of the environment where schools are located, such as level of development, urbanization, and traffic (World Health Organization [WHO] 2006).…”
Section: Discussionsupporting
confidence: 49%
“…Different levels of urbanization and development of the area surrounding schools, meteorological conditions, or seasonal influences might account for some of these differences (Morawska et al, 2009). It is also necessary to indicate that the majority of the existing studies on UFP in educational settings focused on assessments in classrooms (Clausen et al, 2012;Fromme et al, 2007;Guo et al, 2010;Mullen et al, 2011;Norbäck et al, 2011;Weichenthal et al, 2008). Zhang and Zhu (2012) also reported the information on UFP in other school microenvironments: gymnasium, canteen, and libraries.…”
Section: Discussionmentioning
confidence: 99%
“…1). Most of the source emission rate estimation methods (Mitra et al, 2002;Wallace et al, 2004;Mullen et al, 2011) use the concept of mass balance between generation and ventilation removal of the monitored number/mass concentration-size spectrum data. Quite often, this procedure may not be adequate for strong sources such as that due to combustion unless the joint effect of coagulation and ventilation is properly addressed.…”
Section: Methodsmentioning
confidence: 99%